Intracranial Metastatic Neuroblastoma Treated with Gamma Knife Stereotactic Radiosurgery: Report of Two Novel Cases. (19th January 2012) - Rowland, Nathan C.; Andrews, Jennifer; Patel, Daxa; LaBorde, David V.; Nowlan, Adam; George, Bradley; Mazewski, Claire; Reisner, Andrew; Katzenstein, Howard M.
Abstract : Intracranial metastasis of neuroblastoma (IMN) is associated with poor survival. No curative therapy for the treatment of IMN currently exists. Unfractionated radiotherapy may be beneficial in the treatment of IMN given the known radiosensitivity of neuroblastoma as well as its proclivity to metastasize as discrete lesions. We present two patients with IMN treated with Gamma Knife stereotactic radiosurgery (SRS). Single-fraction radiotherapy yielded temporary reduction of tumor burden and stability of disease in both patients. SRS may be a useful palliative tool in the treatment of IMN and expands the overall treatment options for this disease.